Bank credit allocation and sectorial concentration in Mexico: Some empirical evidence - Manuel Ramos-Francia; Santiago García-Verdú (Banco de México, 2017)
We empirically assess the extent to which relative growth rates in labor productivity, output, and wage, and growth in a proxy of firms' concentration can explain relative bank credit growth at a sectorial level in the Mexican economy. To that end, we divide our sectors into two groups based on their average concentration. Then, we estimate a panel regression with fixed effects for each group, positing relative credit growth as dependent variable. We document that changes in concentration growth contribute to explaining relative credit growth, particularly so in the group with high average concentration. However, in the group with low average concentration, relative credit growth seems to be also explained by relative labor productivity, output, and wage growth rates. We also discuss some mechanisms that might explain these results. Such mechanisms could lead to counterproductive dynamics between concentration growth and relative credit growth, for which we provide some empirical evidence.
Keywords: E51; J24; L13; 330; Credit; Concentration; Productivity; Mexico